International research handbook on successful women entrepreneurs - Fielden, Sandra L.; Davidson, Marilyn (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2010)
This informative Handbook examines successful women small business owners in both developed and emergent countries around the globe and, in particular, focuses on women entrepreneur success stories. The contributors expertly identify the issues that underpin the success of women small business owners around the globe.
1. Introduction Sandra L. Fielden and Marilyn J. Davidson 2. Australia Glenice Wood 3. Brazil Andrea E. Smith- Hunter 4. Canada Karen D. Hughes 5. China Jonathan M. Scott, Javed Hussain, Richard T. Harrison and Cindy Millman 6. Denmark Suna Lowe Nielsen, Kim Klyver and Majbritt Rostgaard Evald 7. Fiji Gurmeet Singh, Raghuvar Dutt Pathak and Rafia Naz 8. India Tanuja Agarwala 9. Lebanon Dima Jamali and Yusuf Sidani 10. New Zealand Marianne Tremaine and Kate Lewis 11. Pakistan Jawad Syed 12. Portugal Christina Reis 13. Russia Anna Shuvalova 14. South Africa Babita Mathur-Helm 15. Turkey Mine Karatas-Ozkan, Gozde Inal and Mustafa F. Ozbilgin 16. United Arab Emirates Nnamdi O. Madichie 17. United Kingdom Susan Marlow and Maura McAdam 18. United States of America Mary C. Mattis and Leslie Levin Index..
Originally published: 2010.
&#x000A
Includes bibliographical references and index.
oif 23/05/13
Loan
Keywords: Entrepreneurship. Self-employed women; Women-owned business enterprises; Businesswomen